Edukasi Relaksasi Tarik Napas Dalam pada Penderita Hipertensi di Poli Dalam RSU Siaga Medika Purbalingga - Guntur Susanto; Ita Apriliyani; Mariah Ulfah (Pusat Riset dan Inovasi Nasional, 2025)
Hypertension is a condition in which systolic blood pressure exceeds 140 mmHg and diastolic pressure exceeds 90 mmHg persistently. Uncontrolled high blood pressure can cause disorders in the circulatory system and vital organs such as the heart and brain. One non-pharmacological effort to lower blood pressure in hypertensive patients is through deep breathing relaxation exercises, performed twice a day for ten minutes. RSU Siaga Medika Purbalingga, located in Padamara District, has recorded the highest number of hypertension cases in the area, totaling 4,470 patients. Based on a preliminary survey, many hypertensive patients were unaware of the benefits of deep breathing relaxation therapy; therefore, a Community Service (PkM) activity was conducted in the hospital’s Internal Medicine Clinic. The method involved educational sessions using lectures and demonstrations, supported by leaflets and videos. Participants’ knowledge was evaluated using pretest and posttest questionnaires. The results showed that most respondents were female (60%) and aged between 46–55 years (40%). Knowledge levels significantly improved, from the “low” category (40%) before education to the “good” category (90%) after education. Thus, deep breathing relaxation therapy has the potential to be an effective alternative method to help reduce blood pressure in patients with hypertension.